Optimal green shift, R&D-generated growth, and the risk of environmental disaster - Tapio K. Palokangas (Helsinki Graduate School of Economics, 2025)
Heterogeneous monopolists produce goods using either brown technology, which relies on labor and carbon energy, or green technology, which relies solely on labor. R&D firms enhance productivity using labor to outcompete existing monopolists, thereby driving economic growth. The extraction of carbon energy releases pollutants that harm production and increase the risk of environmental disaster. The government can optimally mitigate the distortions caused by pollution by a two-part Pigouvian tax on carbon energy, with one part being precautionary, applied only before any disaster occurs. When this tax is optimally set, R&D should neither be taxed nor subsidized.
Keywords: H21; O32; O44; Q52; Q54; Q58; 330; R&D; endogenous growth; environmental disaster; precautionary policy